2023
DOI: 10.1002/csc2.20889
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the effects of Striga control methods on maize, sorghum, and major millets production in sub‐Saharan Africa

Abstract: Parasitic Striga weeds severely damage cereal crops in sub‐Saharan Africa (SSA), leading to yield losses in susceptible varieties. A range of Striga control methods are commonly recommended, including cultural practices, chemical herbicides, biological control agents, and host resistance, either as solo treatments or in combinations of these approaches (i.e., integrated Striga management [ISM]). A limited number of studies compared the relative efficacy of the recommended Striga control methods, or their combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Badu-Apraku et al (2010) reported that SDR8, SDR10, EASP, and EPP were the best traits for selection under Striga-infested conditions. SDR was also reported to be the best selection criterion for improving GY performance in maize under Striga infestation by Dossa et al (Dossa et al, 2023). All the traits exhibited high heritability values in both the Sa and Sh environments, except for GY under Shinfested conditions.…”
Section: Principal Component and Biplot Analysesmentioning
confidence: 79%
See 2 more Smart Citations
“…Badu-Apraku et al (2010) reported that SDR8, SDR10, EASP, and EPP were the best traits for selection under Striga-infested conditions. SDR was also reported to be the best selection criterion for improving GY performance in maize under Striga infestation by Dossa et al (Dossa et al, 2023). All the traits exhibited high heritability values in both the Sa and Sh environments, except for GY under Shinfested conditions.…”
Section: Principal Component and Biplot Analysesmentioning
confidence: 79%
“…Striga, popularly known as witchweed, is endemic and widespread throughout SSA. The species S. asiatica (red ower type) is predominant in Southern Africa, and S. hermonthica (purple ower) is widely distributed in Western, Central, and Eastern Africa (Dossa et al, 2023). The two holoparasites cause severe crop damage through stunting and leaf chlorosis, leading to yield losses ranging from 30-100% under severe infestation (Mutsvanga et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield of corn crops varies in relation to biological, economic and environmental factors. Some studies have evaluated the relationship of maize plants, in response to biotic and abiotic factors, in order to identify valuable genetic resources of maize (Dossa et al, 2023). Galic et al (2023), based on extensive studies on a consistent gene bank, communicated results obtained regarding the genetic coding of some proteins or some genes involved in the stress response of plants as well as the genetic diversity of the studied germplasm/ genotypes.…”
Section: Introductionmentioning
confidence: 99%